The Impact of the Design of Cooled Suit in the Recovery and Get Rid of Lactic Acid in the Handball Players in Karbala Club - Hassim Abdul Jabbar Saleh (Journal of Global Pharma Technology, 2018)
The game of handball rely heavily on anaerobic energy production system, and many of the sediments produced when working within the system to produce the necessary muscular contraction of energy, the most important (lactic acid), so the return of the player natural state has become one of the important things to familiarity with them from Before coaches and sports workers. Here lies the importance of research in the design of the suit refrigerated and their impact in the process of healing, which helps restore the player to its natural state, and as soon as possible. The research aimed to design suit refrigerated, and to identify the extent of the efficiency of the suit cooled in the speed of recovery and get rid of lactic acid after the first half and the game players Karbala club handball, and to identify the advantage experimental and control groups in the speed of recovery and get rid of lactic acid after the first half and the game players club Karbala handball. It was the use of the experimental method with the two groups equalizers experimental and control, and select the research community my players Karbala Sports Club handball category of applicants and the number 16 player, "was chosen as a sample of them-style comprehensive inventory after excluding (4) players who are goalkeepers and injured, were divided into Two equal groups Each group includes (6) players. The researchers concluded that the cooled suit is suitable for the recovery process and the elimination of the accumulation of lactic acid. The use of the cooled suit after the first half and the second run hastened the elimination of the accumulation of lactic acid and the healing, and the use of cooled formula is much better than the procedures used by the players and trainers in the process of recovery quick.Keywords: Design, Cooled suit, Recovery, Lactic acid and handball.